Diagnóstico ambiental de las actividades de comercialización, análisis bromatológico y microbiológico de la leche cruda de vaca que se expende en el cantón Santa Rosa Provincia del Oro. - Curimilma Jiménez, Marlene Elizabeth (2016)
Raw cow’s milk is a product of mass and elemental especially in the first years of like for people consumption. Production, quality and sales depend heavily on natural agents many circumstances and factors. Therefore this study was performed initially to environmental characterization in order to determine whether it affects the quality of the milk, natural agents such as time, temperatura, air, wáter, etc.